MP-4 Study of Parasitic Diseases - Goat's Digestive Zoonoses In Gorontalo District - Tri Ananda Erwin Nugroho; Nibras K. Laya; Sarifudin H Hiola; Sarwono S Prasejo; Herman S Wahab (Hemera Zoa, 2018)
The purpose of this study is to study the parasitic-zoonotic diseases of the gastrointestinal tract in goats in Gorontalo District. The results of this study in the long term are expected to contribute to the Gorontalo regional government in the development of the livestock sector, especially in terms of handling diseases in goats and anticipating the presence of goats.